Positive feedback loop mediated by protein phosphatase 1α mobilization of P-TEFb and basal CDK1 drives androgen receptor in prostate cancer - Liu, Xiaming (Nucleic Acids Res, 2017)
P-TEFb (CDK9/cyclin T) plays a central role in androgen receptor (AR)-mediated transactivation by phosphorylating both RNA polymerase 2 complex proteins and AR at S81. CDK9 dephosphorylation mobilizes P-TEFb from an inhibitory 7SK ribonucleoprotein complex, but mechanisms targeting phosphatases to P-TEFb are unclear. We show that AR recruits protein phosphatase 1α (PP1α), resulting in P-TEFb mobilization and CDK9-mediated AR S81 phosphorylation. This increased pS81 enhances p300 recruitment, histone acetylation, BRD4 binding and subsequent further recruitment of P-TEFb, generating a positive feedback loop that sustains transcription. AR S81 is also phosphorylated by CDK1, and blocking basal CDK1-mediated S81 phosphorylation markedly suppresses AR activity and initiation of this positive feedback loop. Finally, androgen-independent AR activity in castration-resistant prostate cancer (CRPC) cells is driven by increased CDK1-mediated S81 phosphorylation. Collectively these findings reveal a mechanism involving PP1α, CDK9 and CDK1 that is used by AR to initiate and sustain P-TEFb activity, which may be exploited to drive AR in CRPC.